PERFORMANCE TEST OF LAB SCALE BATCH FOR ROUGH RICE DRYING USING HUSK OF RICE FUEL - Meylani, Sri Rezeky; ,, Tamrin; ,, Warji; Lanya, Budianto (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2013)
The increase in fuel prices and electricity, husk of rice can be used by farmers as alternative energy for rough rice drying. Mechanical drying such as by using batch dryer can be used to overcome the advantage of sun drying especially in rainning season. This research aim to examine the performance of batch dryer lab scale (capacity of 15 kg - 25 kg of grain) with husk of rice fuel. This research was conducted at three variations of thickness which were 15,3 cm, 20,3 cm, and 25,5 cm. The results showed that the average of drying temperature and moisture content for the treatments were respectivelly, 34,78 °C and 13,97%; 34,20°C and 13,77%; 37,92 °C and 13,67%. The higher temperature used the shorter the drying time and the less thick of rough rice the shorter the drying process. The number of rice husk fuel used for the three different thicknesses were 12 kg, 14 kg and 16 kg, respectivelly. Further, the drying durations for each treatments were 10 hours, 11,3 hours, and 12 hours, respectivelly and the drying efficiencies were 3,05%, 3,41%, and 3.63%, respectivelly. One kg of rice husk could be used to dry about 1,35 kg of wet rough rice. Keywords: Rough rice, Batch dryer, Drying, Fuel, Husk of rice.